The Influence of Soft Skills and Networking on Business Innovation and Startup Sustainability in Indonesia's Creative Industries - T. Lisbet, Zeanette; Supriandi, Supriandi; Muhtadi, Muhamad Ammar (West Science Interdisciplinary Studies, 2025)
The creative industry in Indonesia is a rapidly growing sector that requires continuous innovation and sustainable business practices. This study examines the influence of soft skills and networking on business innovation and startup sustainability using a quantitative approach with Structural Equation Modeling–Partial Least Squares (SEM-PLS). Data were collected from 210 respondents, and the analysis utilized a Likert scale (1-5) to measure perceptions. The findings indicate that soft skills significantly impact business innovation and startup sustainability. Networking also plays a crucial role, positively affecting both business innovation and startup sustainability. The results highlight that entrepreneurs with strong soft skills are more likely to develop innovative strategies, while networking is essential for ensuring long-term sustainability. The study provides managerial insights for entrepreneurs, policymakers, and investors, emphasizing the need for entrepreneurial training programs and networking opportunities to foster business growth in Indonesia’s creative industry.